2010
DOI: 10.4194/trjfas.2010.0110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The proximate compositions and fatty acid profiles of the freshwater mussels Unio terminalis and Potamida littoralis were compared. The crude protein (11.87-11.97%), lipid (2.55-1.05%), ash (1.68-1.61%) and moisture (80.36-81.69%) contents of U. terminalis and P. littoralis were observed. Lipid content of U. terminalis was found to be significantly (P<0.05) higher than in P. littoralis. The percentages of total saturated fatty acids (SFA) and total monounsaturated fatty acids (PUFA) were higher in U. terminali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The long-chain polyunsaturated fatty acids (PUFAs), such as docosapentaenoic acid (DPA), ARA, EPA, and DHA, are well-known for their role in lowing cholesterol levels, reducing coronary heart disease, and preventing inflammation and arteriosclerosis [44,45]. Consistent with the findings from this study, these PUFAs have been previously reported in other marine mollusks [4,43,[46][47][48][49][50][51]. The ratio of n-3 to n-6 fatty acids serves as a valuable indicator of the nutritional value of fatty foods [4].…”
Section: Amino Acid Compositionsupporting
confidence: 90%
“…The long-chain polyunsaturated fatty acids (PUFAs), such as docosapentaenoic acid (DPA), ARA, EPA, and DHA, are well-known for their role in lowing cholesterol levels, reducing coronary heart disease, and preventing inflammation and arteriosclerosis [44,45]. Consistent with the findings from this study, these PUFAs have been previously reported in other marine mollusks [4,43,[46][47][48][49][50][51]. The ratio of n-3 to n-6 fatty acids serves as a valuable indicator of the nutritional value of fatty foods [4].…”
Section: Amino Acid Compositionsupporting
confidence: 90%
“…The n-3/n-6 ratio is recognised as a functional biomedical marker for evaluating the relative nutritional values of lipids derived from the marine sources (Ersoy and Şereflişan, 2010). The n-3 fatty acids regulate hypertension, impair platelet aggregation and inhibit pro-inflammatory and other physiological pathways associated with arterial sclerosis and vulnerable plaques (Anacleto et al, 2014).…”
Section: Notementioning
confidence: 99%